Peran Ibu Asrama Dalam Memenuhi Kebutuhan Penyandang Disabilitas Cerebral Palsy (CP) Di Yayasan Pembinaan Anak Cacat Surakarta - Tasya Nur Azizah; Anastasia Adiwirahayu; Oelin Marliyantoro (Sekolah Tinggi Pembangunan Masyarakat Desa APMD, 2022)
Yayasan Pembinaan Anak Cacat (YPAC) is a form of social service located in Surakarta City as an effort to meet the needs of people with disabilities. YPAC Surakarta has facilities, one of which is dormitory social services. In the YPAC Surakarta dormitory, it is managed by a dormitory mother who is in charge of managing the orphanage, especially the dormitory and also meeting the needs of foster children in the YPAC Surakarta dormitory. Dormitory mothers have an important role in managing orphanages or foundations, especially in meeting needs. The role of boarding house mothers as facilitators, brokers, mediators, defenders, protectors and educators in meeting the needs of people with cerebral palsy with disabilities at YPAC Surakarta, namely fulfilling physiological needs, fulfilling security needs, fulfilling love needs, fulfilling esteem needs and fulfilling self-actualization needs.